Komunikasi Organisasi Dalam Pengelolaan Bantuan Sosial Terhadap Peningkatan Kesejahteraan Masyarakat Desa Di Kabupaten Konawe Selatan - ., Sultrayansa; Lestari, Dian Trianita (CV. ITTC INDONESIA, 2024)
Social assistance is one of the central and regional government programs aimed at improving community welfare, so procedures for implementing social assistance programs must be transparent and consistent in order to achieve community independence. The purpose of this research is to provide an overview of organizational communication in order to improve the welfare of village communities through the provision of social assistance in South Konawe Regency. A qualitative research approach will be used to obtain constructive analysis and supporting data regarding policies implemented by the Social Service regarding the provision of social assistance. The research findings revealed four types of communication used to achieve community welfare goals: Downward communication, Upward communication, Horizontal communication, and Interline communication. These four methods have proven to be effective in distributing social assistance in South Konawe Regency, preventing all types of obstacles such as duplication and providing social assistance that is not intended.